2020
DOI: 10.1021/acs.jafc.0c04821
|View full text |Cite
|
Sign up to set email alerts
|

Urolithins in Human Breast Milk after Walnut Intake and Kinetics of Gordonibacter Colonization in Newly Born: The Role of Mothers’ Urolithin Metabotypes

Abstract: The maternal–infant transmission of several urolithins through breast milk and the gut colonization of infants by the urolithin-producing bacterium Gordonibacter during their first year of life were explored. Two trials (proof-of-concept study: n = 11; validation study: n = 30) were conducted, where breastfeeding mothers consumed walnuts as a dietary source of urolithin precursors. An analytical method was developed and validated to characterize the urolithin profile in breast milk. Total urolithins ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…The type of Uros excreted in breast milk depended on the maternal UM. [7] The profile of metabolites produced by the gut microbiota depends on the host species' characteristics, probably linked to individual differences in the microbiota composition. [8] In previous investigations, nasutin was identified as one of the ET metabolites in rats.…”
Section: 1mentioning
confidence: 99%
“…The type of Uros excreted in breast milk depended on the maternal UM. [7] The profile of metabolites produced by the gut microbiota depends on the host species' characteristics, probably linked to individual differences in the microbiota composition. [8] In previous investigations, nasutin was identified as one of the ET metabolites in rats.…”
Section: 1mentioning
confidence: 99%
“…Adlercreutzia equolifaciens is an equol-producing bacterium [ 28 ]. It was found that Adlercreutzia was predominant in individuals characterized by urolithin A production [ 29 ]. Whether it is also involved in urolithin production requires further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this difference in microbiota composition would further influence the health benefits associated with ellagitannin-rich food ( 34 ). Notably, urolithins have been found in breast milk of mothers, who consume ellagitannin rich walnut, and it resembles Urolilithin metabotypes of the mothers as well ( 35 ). Investigations on how these bacteria can improve the metabolism of an ellagitannin-rich food, how would it further bring about health benefits, and an examination of its safety aspects are vital before considering them as a potential probiotic.…”
Section: Colon Bacteria: the Cooks Who Brought Out The Delicacymentioning
confidence: 99%